Analisis Kebutuhan E-Portofolio Berbasis Metakognisi untuk Meningkatkan Ketrampilan Abad 21 - Marheny Lukitasari; Jeffry Handhika; Wasilatul Murtafiah (Universitas Sebelas Maret, 2016)
The aim of this research is profiling the use of e-portfolios within metacognition based science learning to improve 21st century skills. Profiling is done through observation towards: 1) students’ metacognition awareness, 2) understanding of portfolio and e-portfolio, 3) administrative tasks, 4) process of giving tasks from lecturer. The samples in this study are four lecturers and eighty-seven students of FPMIPA IKIP PGRI Madiun. The instrument that used is questionnaire. The data are analyzed with descriptive qualitative using triangulation and strengthening of reference. The results of the study inform; 1) students’ metacognition awareness is in low at 55,17%, 2) students’ understanding about the portfolio and e-portfolio is still low at 57,47% dan 62,07%, which is inversely proportional to the ability of IT by 86.20%, 2) 35.48% students file neatly the assignment in softcopy, 3) two of four lecturers familiarize students to upload the assignments via internet. Based on needs analysis, it is required to use e-portfolio software with the basis of metacognition to support the lecture, in order to improve 21st century skills for students. Keywords: needs analysis, e-portofolio, metacognition, 21st century skills